Urban Design Concept for Achieving a Livable Balinese Town - Samadhi, Tjokorda Nirarta (Journal of Regional and City Planning, 2001)
This research considers the utilization of a number of Balinese cultural constants as basis of the development of urban design concepts for producing culturally livable places in the Balinese town of Gianyar. The concept of  ‘livable place or city’ connotes, among other, the need of a ‘sense of ‘place’. A pluralistic approach, by means of questionnaires and mental map sketching techniques was employed to reveal some cultural constants in the cultural landscapes of a contemporary Gianyar urban setting. This exploration aims at providing a ground for reconnecting urban design proposals with their cultural context, this promoting the spatially expressed localism which originates from the diversity of cultures to ultimately produce ‘a sense of place’. The research concludes that to achieve culturally appropriate sense of place, hence a livable town, the design process has to acknowledge finer core cultural constants in the design of  Balinese townscapes: 1) attitude to human being-environment relationship; 2) the concept Of center; 3) attitude to spatial organization and structure; 4) attitude to environmental design and management; and 5) attitude to symbols and meanings. Within the framework of urban design principles and town’s identity elements. a series of urban design concepts is composed. Based upoir such concepts, urban spatial organization, structure and form will significantly reflect the Balinese cultural identity.